2012
DOI: 10.1007/s12070-011-0467-4
|View full text |Cite
|
Sign up to set email alerts
|

Is Transnasal Endoscopic Examination Necessary Before and After Adenoidectomy?

Abstract: The present study aimed to investigate the amount of residual adenoid tissue following the conventional adenoidectomy as compared with preoperative values. A total of 32 girls and 44 boys (range, 3-15 years) in whom adenoidectomy procedure was planned were included in the study. Adenoid tissue sizes before adenoidectomy and residual tissue sizes after conventional curettage adenoidectomy were measured by transnasal endoscopic examination and were recorded. Adenoid tissue size before and after adenoidectomy was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 10 publications
0
7
0
Order By: Relevance
“…In 5 out of 10 operated children, the authors reported no complete removal of the tonsil in the radiological examination. This is much more than that described by other authors assessing the surgical effects of adenoidectomy (e.g., with endoscopic examination) [ 22 ]. Moreover, it has also been proven that evaluation of adenoid size by cephalometric radiography is much less effective than CT, and what was mentioned above overestimated the adenoid size [ 19 , 23 ].…”
Section: Discussionmentioning
confidence: 83%
See 2 more Smart Citations
“…In 5 out of 10 operated children, the authors reported no complete removal of the tonsil in the radiological examination. This is much more than that described by other authors assessing the surgical effects of adenoidectomy (e.g., with endoscopic examination) [ 22 ]. Moreover, it has also been proven that evaluation of adenoid size by cephalometric radiography is much less effective than CT, and what was mentioned above overestimated the adenoid size [ 19 , 23 ].…”
Section: Discussionmentioning
confidence: 83%
“…[ 34 , 35 ]. It is also dependent on the surgeon’s experience and surgical technique [ 22 , 34 ]. Yildirim shows that blind curettage adenoidectomy may have left in 18% large residual adenoid.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several adenoidectomy techniques have been described in the literature. The most common and classical adenoidectomy method is blindly transoral removal of the adenoid tissue with an adenoid curette or adenotome [1,3,4]. After conventional curettage adenoidectomy, residual adenoid tissue may remain.…”
Section: Introductionmentioning
confidence: 99%
“…After conventional curettage adenoidectomy, residual adenoid tissue may remain. Therefore, alternative surgical methods have been described [3,4].…”
Section: Introductionmentioning
confidence: 99%